Criminal Confrontation for the Crime of Stealing Antiquities - A Comparative Study - Assistant Lecturer Marwan Hussein Ahmed., (The college of law and political science journal, 2023)
Criminal Confrontation for the Crime of Stealing Antiquities - A Comparative Study